Development of a new 17 Y-STRs system using fluorescent-labelled universal primers and its application in Shanxi population in China. Issue 1 (December 2019) - Liu, Jinding; Wang, Rongshuai; Hao, Ting; Cheng, Xiaojuan; Guo, Jiangling; Yun, Keming; Yan, Jiangwei; Zhang, Gengqian
Highlights: A new 17 Y-STR system was developed for human identification and paternity testing. Universial fluorescent-labeled primer was used to develop a panel, which amplicons range from 126bp to 400bp. A population study with 394 unrelated individual from Shanxi Han of China was performed using this panel. Abstract: Y-chromosomal short tandem repeats (Y-STRs) polymorphisms are useful in forensic identification, population genetics and constructing of human structures. Increasing the number of Y-STRs and their polymorphism will drastically narrow down the matching number of genealogy populations or pedigrees when searching against a forensic DNA databank. In this study, we develop a system containing 17 complementary Y-STRs that are compatible and reinforce the current commercially available Y-STR kits. This system was constructed by multiplex PCR with expected size of 126bp-400bp using home-made universal primers labeled by different fluorescence (DYS715, DYS709, DYS716, DYS713, DYS607, DYS718, DYS723, DYS708, DYS714, DYS712, DYS717, DYS721, DYS605, DYS719, DYS726, DYS598 and DYS722). The genetic data were obtained from 394 individuals in Shanxi province, China. The Y-STR system has 131 haplotypes and high discrimination power is 1. In conclusion, our study provides a robust, sensitive and cost-effective genotyping method for human identification, which is beneficial for narrowing the searching scope when applying to the genealogy searching with Y-STR DNA databank.